Implementasi E-Book dengan Pendekatan PjBL dalam Meningkatkan Literasi Matematis Siswa SMA Muhammadiyah 11 Kota Padangsidimpuan - Siregar, Yulia Anita; Darwis, Muhammad; Harahap, Eli Marlina; Hanum, Yuwinda Habibah; Putri, Radika (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine whether the use of e-books with a Project-Based Learning (PjBL) approach can improve the mathematical literacy of students at Muhammadiyah 11 Senior High School in Padangsidimpuan City. The research method used was quantitative with an experimental design involving two groups: an experimental group using e-books based on the PjBL approach and a control group using conventional learning, with a total of 60 students. Data were collected through a mathematical literacy test based on story problems and a questionnaire about the e-book and PjBL learning. Data analysis techniques included normality and homogeneity tests, t-test, N-Gain test. The results showed that the experimental group experienced an increase in scores from a pretest of 52.3 to a posttest of 78.5, with an N-Gain value of 0.55 (moderate category). In contrast, the control group improved from 51.8 to 66.2, with an N-Gain of 0.34 (low category). This indicates that using PjBL-based e-books is more effective in enhancing students' mathematical literacy compared to conventional learning.